School caringscapes: Understanding how time and space shape refugee and immigrant adolescents’ caring practices and wellbeing in Danish schools - Anne Sofie Borsch; Kathrine Vitus; Morten Skovdal (Wellbeing, Space and Society, 2021)
Schools are increasingly cited as spaces of support for learners facing adversity. It is therefore not surprising that recent migration flows have contributed to a mushrooming of school-focused policies and interventions looking to promote the mental health and wellbeing of refugee and immigrant learners. In response to a research focus on how teachers, schools and school-based interventions care for the wellbeing of vulnerable leaners, this article explores ethnographically how school-going refugee and immigrant adolescents develop their own practices of care for self and others. It draws on fieldwork carried out between December 2018 and June 2019 and includes participant observations in two Danish preparatory classes for newcomers and in-depth interviews with 13 learners and five teachers. Drawing on the concepts of caringscapes and carescapes, our analysis not only reveals how newcomers form significant caring practices, and co-produce spaces that foster collective wellbeing, but highlights the temporally and spatially bounded nature of their care. We found their caring practices to be oriented in relation to biographical time, highlighting how newcomers enrol past experiences, present needs and future aspirations in their caring. We also noted that newcomers’ caring practices are contingent on the character of their school environments, including teacher practices, and wider policy contexts around refugee and immigrant children's education and residence. We conclude that efforts to understand and promote refugee and immigrant learners’ wellbeing in school contexts must take heed of the temporally and spatially bounded nature of their agentic capabilities to care for themselves and their peers.